Efeitos de diferentes percentuais de sementes esverdeadas na qualidade fisiológica de lotes de sementes de soja - Arruda, Marcia Helena Mota de (2013)
Brazil increased 9 % the production of soybeans during 2012/2013 crop. Since 2006, the state of Tocantins grow soybeans during a period called sanitary empty as exceptionalism. This production is destined for research or for seed. However, frequentlly, it was observed the presence of green seed at harvest. This release to produce soybean seed during sanitary empty, issued by the Ministry of Agriculture, Livestock and Supply, is due to climate and land conditions found in the municipalities of Lagoa da Confusão, Dueré and Formoso do Araguaia. This study was conducted to evaluate the effect of the occurrence in quality of green seeds in soybean seed lots. Four lots of the cultivar M-SOY 8866, medium cycle, produced in Formoso do Araguaia, state of Tocantins (TO) were used in this study. The lots were selected by visual presence of green seed with a 6X magnifying glass. The lots showed 17 %, 36 %, 49 % green seeds and were named respectively Lot 1, 2, 3 and control (lot with no green seeds). Seed quality was monitored through the thousand seed weight, germination in rolled paper with and without preconditioning, the tetrazolium test and the emergency field tests. The experimental design was a randomized complete block design with four seed lots and five replicates and the averages compared by Tukey test at 5 %. The results show a decrease in the percentage of germination and vigor in all plots when compared to the test, observed primarily by moisture damage in the tetrazolium, field emergence and germination test preconditioning 24 h test.